The study of the properties of the extended Higgs boson sector within hMSSM model - Obikhod, T.V.; Petrenko, E.A. (Вопросы атомной науки и техники, 2019)
Using the latest experimental data, performed by ATLAS Collaboration and within the framework of the Minimal Supersymmetric Standard Model, we presented the calculations for cross sections times branching fractions, σ × Br, as a functions of the CP-even, H, Higgs boson mass, CP-odd, A, Higgs boson mass and charged, H±, Higgs boson mass. Using the restricted parameter set, received from the hMSSM+HDECAY and ”low-tb-high” scenarios, with the help of the computer programs SOFTSUSY, Prospino and SusHi, we received the large values of σ × Br for A and H bosons at tanβ=2 for the planned 14 TeV at the LHC and found the large σ × Br at tanβ=30 for charged Higgs boson. The obtained results are of experimental interest as they are connected with the experimental searches for new physics beyond the Standard Model at the LHC. Використовуючи останні експериментальні дані, отримані ATLAS колаборацією, у рамках Мінімальної суперсиметричної стандартної моделі, ми представили розрахунки по перерізам утворення, помноженим на ширини розпадів, σ × Br, як функції маси СР-парного, H, бозона Хіггса, СР-непарного, A, бозона Хіггса і зарядженого, H±, бозона Хіггса. Використання обмеженого набору параметрів, отриманих з hMSSM + HDECAY і «low-tb-high» сценаріїв, за допомогою комп'ютерних програм SOFTSUSY, Prospino і SusHi, дало можливість отримати великі значення σ × Br задля А і Н бозонів при tanβ=2 для запланованих 14 ТеВ на LHC і велике значення σ × Br при tanβ=30 для зарядженого бозона Хіггса. Отримані результати є важливими для експеримента, оскільки вони пов'язані із експериментальними пошуками нової фізики за межами Стандартної моделі на LHC. Используя последние экспериментальные данные, полученные ATLAS коллаборацией, в рамках Минимальной суперсимметричной стандартной модели, мы представили расчеты по сечениям, умноженным на ширины распадов,σ × Br, как функции массы СР-четного, H, бозона Хиггса, СР-нечетного, A, бозона Хиггса и заряженного,H±, бозона Хиггса. Использование ограниченного набора параметров, полученных из hMSSM + HDECAY и «low-tb-high» сценариев, с помощью компьютерных программ SOFTSUSY, Prospino и SusHi, дало возможность получить большие значения σ × Br для А и Н бозонов при tanβ=2 для запланированных 14 ТэВ на LHC и большое значение σ × Br при tanβ=30 для заряженного бозона Хиггса. Полученные результаты представляют собой интерес для эксперимента, поскольку они связаны с экспериментальными поисками новой физики за пределами Стандартной модели на LHC.